The influence of oceanographic features on the foraging behavior of the olive ridley sea turtle Lepidochelys olivacea along the Guiana coast. (March 2016) - Chambault, Philippine; de Thoisy, Benoît; Heerah, Karine; Conchon, Anna; Barrioz, Sébastien; Dos Reis, Virginie; Berzins, Rachel; Kelle, Laurent; Picard, Baptiste; Roquet, Fabien; Le Maho, Yvon; Chevallier, Damien
Highlights: Migratory tracks and diving behavior of 18 adult female olive ridley turtles during migration from French Guiana. Quantification of the relationships between foraging behavior and (a) oceanographic features, (b) micronekton biomass. Remote sensing data showed a productive area influenced by the Amazon River plume and characterized by anticyclonic eddies. Horizontal foraging strategies were related to high micronekton biomass and low current velocities. Vertical foraging strategies were linked to the thermocline depth. Abstract: The circulation in the Western Equatorial Atlantic is characterized by a highly dynamic mesoscale activity that shapes the Guiana continental shelf. Olive ridley sea turtles ( Lepidochelys olivacea ) nesting in French Guiana cross this turbulent environment during their post-nesting migration. We studied how oceanographic and biological conditions drove the foraging behavior of 18 adult females, using satellite telemetry, remote sensing data (sea surface temperature, sea surface height, current velocity and euphotic depth), simulations of micronekton biomass (pelagic organisms) and in situ records (water temperature and salinity). The occurrence of foraging events throughout migration was located using Residence Time analysis, while an innovative proxy of the hunting time within a dive was used to identify and quantify foraging events during dives. Olive ridleys migrated northwestwards using the Guiana current and remained on the continental shelf at the edge of eddies formed by the North Brazil retroflection, an area characterized by low turbulence and high micronekton biomass. They performed mainly pelagic dives, hunting for an average 77% of their time. Hunting time within a dive increased with shallower euphotic depth and with lower water temperatures, and mean hunting depth increased with deeper thermocline. This is the first study to quantify foraging activity within dives in olive ridleys, and reveals the crucial role played by the thermocline on the foraging behavior of this carnivorous species. This study also provides novel and detailed data describing how turtles actively use oceanographic structures during post-nesting migration.